The proliferation of informal sector activities in Congo: Case of the city of Brazzaville - KEVIN, NZOUSSI; Feng, Li Jiang (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2017)
The underground of the countries of Africa south of the Sahara is full of enormous potentialities and raw materials of all kinds. But the population of Africa in general and of Africa south of the Sahara, in particular, remains the poorest in the world. A contrast which can be justified by the political and economic instability, the corollary of which is poor management, the drop in the standard of living. The economic potential of these countries does not reflect the level of populations that generally languish in enormous poverty without real livelihoods. Beginning in the 1980s, a large-scale economic crisis shook virtually all African countries because of the stringent restrictions and measures imposed by the Bretton Woods institutions, notably the International Monetary Fund and the World Bank. In order to cope with the increasingly difficult living conditions, the populations of which were the main victims, that is to say, the populations will gradually organize themselves and several activities will emerge. These activities are part of the informal sector. It is, therefore, a sector that brings together unemployed people looking for employment and societal well-being who organize themselves to face everyday problems. This means that it is a lucrative sector that is constantly absorbing unemployment in Congo in general and Brazzaville in particular.